Spectroscopic characterization and evaluation of the sensing ability of a bis-indolylmethane as a new colorimetric chemosensor for cations - Fernandes, Mónica C. S. (2016)
Comunicação em painel P10 no IV Encontro em Técnicas de Caracterização e Análise Química, 17 de junho 2016, Braga, Portugal.